PEMBERDAYAAN PETERNAK MELALUI PENGENALAN AYAM KUB DAN FORMULA RANSUM BERBAHAN LOKAL DI NAGARI ANDALEH KABUPATEN TANAH DATAR - Reski, Sepri; Pazla, Roni; Madarisa, Fuad; Firdani, Fea; Putra, Aldiansyah; Optapia, Yana; Chatimah, Husnil (Jurnal Hilirisasi IPTEKS, 2025)
One of the main challenges in KUB chicken farming is the high cost of feed. To address this issue, an innovative approach to feed formulation is required, utilising efficient and cost-effective local ingredients. The objective of this activity was to introduce KUB chickens and the process of creating locally-sourced feed formulas to farmers in Nagari Andaleh, Tanah Datar Regency, through student-led activities integrated with the MBKM (Freedom to Learn – Independent Campus) programme. This activity took place in Nagari Andaleh, Batipuh Subdistrict, Tanah Datar Regency, West Sumatra Province. The methods employed included extension and training sessions. The extension activities covered the potential and advantages of KUB chickens, as well as their management. The training sessions involved hands-on demonstrations of how to formulate feed using local ingredients, which are more economical than commercial feeds. Additionally, 100 KUB chicks were distributed as assistance to the farmers. The outcomes of the activity included improved knowledge, understanding, and skills among participants in utilising the potential of KUB chickens and locally-sourced, cost-effective feed. This has had a positive impact on the development of livestock enterprises. Furthermore, participants demonstrated a better understanding of proper KUB chicken management practices. In conclusion, this activity successfully enhanced the participants’ understanding and skills in making use of the potential of KUB chickens and economical feed alternatives, contributing positively to the development of livestock farming in Nagari Andaleh, Tanah Datar Regency.